2008
DOI: 10.4049/jimmunol.181.4.2506
|View full text |Cite
|
Sign up to set email alerts
|

γc-Signaling Cytokines Induce a Regulatory T Cell Phenotype in Malignant CD4+ T Lymphocytes

Abstract: In this study, we demonstrate that malignant mature CD4+ T lymphocytes derived from cutaneous T cell lymphomas (CTCL) variably display some aspects of the T regulatory phenotype. Whereas seven cell lines representing a spectrum of primary cutaneous T cell lymphoproliferative disorders expressed CD25 and TGF-β, the expression of FOXP3 and, to a lesser degree, IL-10 was restricted to two CTCL cell lines that are dependent on exogeneous IL-2. IL-2, IL-15, and IL-21, all of which signals through receptors containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 41 publications
7
63
0
4
Order By: Relevance
“…By its feature of being constitutively expressed and activated, NPM/ ALK secures a persistent, steady expression of the CD274 protein by the ALKϩTCL cells. Considering our previous findings that NPM/ALK also induces expression of IL-10 and TGF-␤ (17), although not FoxP3, as we have clarified recently (22), these combined observations indicate that inhibition of immune response against ALKϩTCL cells is an important component of the NPM/ALK-mediated oncogenicity. It is also very interesting that NPM/ALK induces expression of these immunosuppressive proteins through STAT3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By its feature of being constitutively expressed and activated, NPM/ ALK secures a persistent, steady expression of the CD274 protein by the ALKϩTCL cells. Considering our previous findings that NPM/ALK also induces expression of IL-10 and TGF-␤ (17), although not FoxP3, as we have clarified recently (22), these combined observations indicate that inhibition of immune response against ALKϩTCL cells is an important component of the NPM/ALK-mediated oncogenicity. It is also very interesting that NPM/ALK induces expression of these immunosuppressive proteins through STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…NPM/ALK-expressing SUDHL-1, JB6, SUP-M2, Karpas 299, and L-82 cell lines were derived from ALKϩTCL patients (10,(15)(16)(17)(18). IL-2-dependent T cell line Sez-4 and IL-2-independent MyLa3675 were derived from a CTCL patient (21,22). Jurkat was developed from lymphoblastic T-cell lymphoma.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression profiling studies have shown that increased signaling from the TCR can be considered a driving force of CTCL and that neoplastic T cells can show a degree of phenotypic plasticity, as characterized by the expression of a variety of lineage markers. [5][6][7][8][9] However, whether this is the result of signaling from the tumor stroma or the consequence of specific genetic alterations in the pathways involved in TCR signaling is still a matter of active research. [10][11][12] Early stages of CTCL are treated with combinations of UV and immunotherapy, with mono-or polychemotherapy being reserved for cases that do not respond to previous treatment.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,19 Although it is not easy to fit ALK ϩ TCL into a specific functional CD4 ϩ T-cell subset considering the sometime overlapping features of the subsets and malignant, aberrant phenotype of the ALK ϩ TCL cells, it can be argued that the lymphoma cells resemble type 1 subcategory of Treg cells because of the production of large amounts of IL-10 and lack of expression of FoxP3. 12,21 Of note, ALK ϩ TCL also express an immunosuppressive cell-surface protein PD-L1 10 ; but in contrast to IL-10 and FoxP3 expression, PD-L1 has not so far been associated with any given category of normal Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 IL-2-dependent T-cell lines Sez-4 and SeAx and IL-2-independent Myla2059 and MyLa3675 were derived from CTCL, and PB-1, 2A, and 2B were derived from a patient with a primary skin CD30 ϩ lymphoproliferative disorder. 11,12 Jurkat cell line was developed from lymphoblastic T-cell lymphoma. The Epstein-Barr virus (EBV)-negative cell lines, Ly18 and Val, were derived from diffuse large B-cell lymphoma and Ramos from Burkitt lymphoma.…”
Section: Cells and Tissue Samplesmentioning
confidence: 99%